2019
DOI: 10.1007/s12105-019-01038-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 19 Immunostain Reduces Variability in Grading Epithelial Dysplasia of the Non-Keratinized Upper Aerodigestive Tract Mucosa

Abstract: Epithelial dysplasia (ED) grading systems are criticized for low reliability. The effects of diagnostic tests or stains on reducing examiner variability in grading ED of the upper aerodigestive tract have not been investigated. The study aim was to examine the effectiveness of cytokeratin 19 (K19) immunostain on enhancing inter and intraexaminer reliability of ED grading and to reiterate the relation of K19 positivity with epithelial keratinization. The study sample consisted of 122 paraffin blocks that fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…None of the studies have managed to investigate the effectiveness of keratin as a diagnostic utility; that is, the improvement of inter- and intra-observer reliability with the utility of keratin is needed. This has been recently achieved in sites involving the upper aerodigestive tract, whereby the authors utilized the suprabasal extension of K19 to improve inter- and-intra observer reliability for the diagnosis of dysplasia [ 75 ]. The closest study in this review to achieving this was Becker [ 28 ], who reportedly used K13 and K17 to improve diagnosis of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies have managed to investigate the effectiveness of keratin as a diagnostic utility; that is, the improvement of inter- and intra-observer reliability with the utility of keratin is needed. This has been recently achieved in sites involving the upper aerodigestive tract, whereby the authors utilized the suprabasal extension of K19 to improve inter- and-intra observer reliability for the diagnosis of dysplasia [ 75 ]. The closest study in this review to achieving this was Becker [ 28 ], who reportedly used K13 and K17 to improve diagnosis of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of immunohistochemistry and other biomarkers to improve and support the histological assessment and prediction of the progression of SILs and/or risk for development of cancer has virtually no practical value. A more recent study used cytokeratin 19 and concluded reduced inter-and intra-examiner variability [68]. This study was however performed on dysplastic lesions of the upper aerodigestive tract as a whole and on non-keratinising epithelia only.…”
Section: Key Summary Pointsmentioning
confidence: 99%